Exploration of Thiazolo[5, 4‐d]thiazole Linkages in Conjugated Porous Organic Polymers for Chemoselective Molecular Sieving. Issue 42 (28th June 2018) - Biswal, Bishnu P.; Becker, Daniel; Chandrasekhar, Naisa; Seenath, Jensheer Shamsudeen; Paasch, Silvia; Machill, Susanne; Hennersdorf, Felix; Brunner, Eike; Weigand, Jan J.; Berger, Reinhard; Feng, Xinliang
Abstract: Porous organic polymers (POPs) have attracted significant attention towards molecular adsorption in recent years due to their high porosity, diverse functionality and excellent chemical stability. In this work, we present a systematic case study on the formation of thiazolo[5, 4‐ d ]thiazole (TzTz) linkages through model compounds and its integration to synthesize a set of three novel, thermo‐chemically stable TzTz‐linked POPs, namelyTzTz‐POP‐3, TzTz‐POP‐4, andTzTz‐POP‐5 with triphenylbenzene, tetraphenylpyrene and tetra(hydroxyphenyl)methane cores, respectively. Interestingly, the integrated TzTz moiety of the representedTzTz‐POP‐3 renders chemoselective removal of organic dye fluorescein (FL) from a mixture with parafuchsine (FU) in aqueous solution. TheTzTz‐POP‐3 offered excellent chemoselectivity of ≈1:7 (FL:FU), compared to alike porous materials demonstrated for similar applications due to the presence of multiple active anchoring sites coupled with permanent porosity and appropriate pore window. Abstract : Polymer pops ! Three novel, thermo‐chemically stable TzTz‐linked POPs, namelyTzTz‐POP‐3, TzTz‐POP‐4, andTzTz‐POP‐5 have been synthesized. Interestingly, the integrated TzTz moiety of the representedTzTz‐POP‐3 renders chemoselective removal of organic dye fluorescein (FL) from a mixture with parafuchsin (FU) in aqueous solution. TheTzTz‐POP‐3 offered excellent chemoselectivity of ≈1:7 (FL:FU), compared to alike porous materials demonstrated for similar applications due to the presence of multiple active anchoring sites coupled with permanent porosity and appropriate pore window.